Relationship of age, prostate-specific antigen, and prostate volume in Indonesian men with benign prostatic hyperplasia - Putra, Ida Bagus O.W.; Hamid, Agus R.A.H.; Mochtar, Chaidir A.; Umbas, Rainy (Prostate international, 2016)
To investigate the relationship between age, prostate specific antigen (PSA), and prostate volume (PV) in Indonesian men with histologically proven benign prostatic hyperplasia. Data were generated from our BPH database from June 1994 until December 2013. Subjects were men with a minimum age of 40 years with chief complaint of LUTS or urinary retention, diagnosed with BPH. All patients underwent TRUS-guided prostate biopsy. Patients with PSA level >10 ng/mL were excluded from the study to exclude the possibility of occult prostate cancer. PV was measured with TRUS. Appropriate statistical tests were employed for data analysis. In all, 1638 patients were enrolled in our study. There was a statistically significant difference in PSA (P = 0.03) and PV (P < 0.0001) between age groups. Overall correlation between age, PSA, and PV were: i). Age and PV (r = 0.12, P < 0.0001); ii). Age and PSA (r = 0.07, P = 0.008); iii). PSA and PV (r = 0.26, P < 0.0001). Subgroup analysis in terms of indwelling catheter use versus without: i). Age 66.09 ± 8 years versus 65.38 ± 7.66 years (P = 0.158); ii). PSA 4.93 ± 2.62 ng/mL versus 4.68 ± 2.82 ng/mL (P = 0.038); iii). PV 47.58 ± 21.33 mL versus 41.43 ± 20.55 mL (P < 0.0001). Correlation between age, PSA, and PV in patients were similar in patients with and without indwelling catheter. In Indonesian men with biopsy-proven BPH, both PV and PSA increased with ageing. Prostate volume was significantly correlated with PSA. Even though the results were weaker, these results are consistent with results in other sets of population. The results vary between different countries and thus, ethnicities. Indonesia is a populous a sociocultural and ethnically diverse country. Therefore, aside from PSA, age, and PV, when investigating men with BPH, ethnicity may also need to be taken into account.